ANALISIS YURIDIS TERHADAP PERTIMBANGAN HAKIM DALAM MENENTUKAN BERAT RINGANNYA PIDANA DALAM TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN (STUDI KASUS PUTUSAN NOMOR 373/PID.B/2020/PN.PDG) - Husnul Khotimah; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The main problem in this study is how the judge's consideration in making a decision onthe criminal act of persecution that resulted in death in the decisionNumber.373/Pid.B/2020/Pn.Pdg. The purpose of this thesis is first, to find out the suitability ofthe judge's considerations which declared the defendant guilty of committing a criminal act ofpersecution that resulted in death with the actions that the defendant did in the decision Number373/Pid.B/2020/Pn.Pdg. Second, furthermore, to find out the suitability of the criminalimposition by the judge in case Number. 373/Pid.B/2020/Pn.Pdg in terms of the purpose ofpunishment.This study uses a normative juridical approach, in this study focused on the study of legalprinciples, especially on the principle of justice in Case Number 373/Pid.B/2020/Pn.Pdg. theapproach taken is to use descriptive qualitative analysis techniques, in data collection used themethod of literature review. The data sources used are primary and secondary legal materials.The conclusions obtained from the results of the study are first, the judge's considerationin the decision Number 373/Pid.B/2020/Pn.Pdg is not in accordance with the actions that thedefendant did. The judge did not consider the non-juridical aspects of the defendant, and theelements in Article 8 paragraph (2) No 48 of 2009 concerning Judicial Power and the elementsof Article 48 and Article 49 of the Criminal Code, especially the element of self-defense, thejudge also did not consider the position of the accused at that time as a security guard whocarried out his duties. Second, the judge's decision (case study Number 373/Pid.B/2020/Pn.Pdg)is not in accordance with the purpose of sentencing, the decision is contrary to the purpose ofsentencing, the defendant cannot be said to be a criminal and the defendant's actions cannot besaid to be a bad act. so that there is no reason or purpose of sentencing that can justify theconviction of the defendant.Keywords: Consideration- Judge- Heavy- Lightness-Criminal